Isolation and characterization of 19 novel microsatellite loci in Rhododendron aureum and Rhododendron brachycarpum (Ericaceae). (August 2015) - Kwak, Myounghai; Won, Hyosig; Hong, Jaram; Lee, Byoung Yoon
Abstract: Nineteen polymorphic microsatellite loci are described for Rhododendron aureum Georgi (Ericaceae), an endangered species in Korea, and the closely related Rhododendron brachycarpum . The sequences containing repeat motifs were identified using low-depth next generation sequencing and 148 microsatellite loci were examined for amplification success and the detection of polymorphisms. All 19 loci were polymorphic and the number of alleles for these markers varied from 4 to 25, with an average of 15 alleles per locus. Three R . aureum loci showed departure from Hardy–Weinberg equilibrium (HWE) and one R . brachycarpum locus deviated significantly from HWE. These microsatellite loci will be useful for investigating the genetic diversity and population structure of both species. Highlights: Rhododendron aureum and it closely related Rhododendron brachycarpum were investigated. Using low-depth next generation sequencing, di-/tri-repeats were identified. Nineteen polymorphic loci were identified with an average of 15 alleles per locus.